Renewal in the Workplace : A Critical Look at Collective Bargaining - Craig, Alton W.J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Renewal in the Workplace : A Critical Look at Collective Bargaining," by Harry Antonides.